Persistence of auditory modulation of wind-induced escape behavior in crickets - Lu, Anhua; Fukutomi, Matasaburo; Shidara, Hisashi; Ogawa, Hiroto (Frontiers in Physiology, 2023)
Animals, including insects, change their innate escape behavior triggered by a specific threat stimulus depending on the environmental context to survive adaptively the predators’ attack. This indicates that additional inputs from sensory organs of different modalities indicating surrounding conditions could affect the neuronal circuit responsible for the escape behavior. Field crickets, Gryllus bimaculatus, exhibit an oriented running or jumping escape in response to short air puff detected by the abdominal mechanosensory organ called cerci. Crickets also receive a high-frequency acoustic stimulus by their tympanal organs on their frontal legs, which suggests approaching bats as a predator. We have reported that the crickets modulate their wind-elicited escape running in the moving direction when they are exposed to an acoustic stimulus preceded by the air puff. However, it remains unclear how long the effects of auditory inputs indicating surrounding contexts last after the sound is terminated. In this study, we applied a short pulse (200 ms) of 15-kHz pure tone to the crickets in various intervals before the air-puff stimulus. The sound given 200 or 1000 ms before the air puff biased the wind-elicited escape running backward, like the previous studies using the longer and overlapped sound. But the sounds that started 2000 ms before and simultaneously with the air puff had little effect. In addition, the jumping probability was higher only when the delay of air puff to the sound was 1000 ms. These results suggest that the cricket could retain the auditory memory for at least one second and alter the motion choice and direction of the wind-elicited escape behavior.